2021
DOI: 10.1080/21655979.2021.1930335
|View full text |Cite
|
Sign up to set email alerts
|

Trichosanthin inhibits cervical cancer by regulating oxidative stress-induced apoptosis

Abstract: Based on many studies, trichosanthin (TCS) has an antiviral effect that regulates immune response, and targets cancer cells to exert broad-spectrum anti-tumor pharmacological activities. It is speculated that TCS may be a potential natural active drug for preventing as well as treating cervical cancer. But the clearer impact along with underlying TCS mechanism on cervical cancer are still unclear. The purpose of this study is to investigate the function and potential mechanism of TCS in cervical cancer. We mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 37 publications
0
20
0
1
Order By: Relevance
“…Following cell cultivation in the dark at 4°C for 30 min, the Invitrogen Attune NXT flow cytometry (Catalog. number was A24863, Thermo Fisher Scientific, Shanghai, China) was manipulated to monitor apoptosis [ 27 ]. Through computer algorithm processing, the percentage of apoptosis was worked out.…”
Section: Methodsmentioning
confidence: 99%
“…Following cell cultivation in the dark at 4°C for 30 min, the Invitrogen Attune NXT flow cytometry (Catalog. number was A24863, Thermo Fisher Scientific, Shanghai, China) was manipulated to monitor apoptosis [ 27 ]. Through computer algorithm processing, the percentage of apoptosis was worked out.…”
Section: Methodsmentioning
confidence: 99%
“…Previous reports have confirmed that miR-582-3p contributes to poor prognosis of NSCLC patients by activating the Wnt/β-catenin signaling pathway [ 37 ]. In our report, to explore the role of miR-582-3p in A549 cells, miR-582-3p inhibitor or inhibitor control were transfected into A549 cells.…”
Section: Resultsmentioning
confidence: 92%
“…no. KA3805; Abnova) was used to detect apoptosis according to the manufacturer’s instructions ( https://www.abcam.com/protocols/annexin-v-detection-protocol-for-apoptosis ) [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…MMP was measured by JC-1 method as previous study [ 26 ]. Briefly, the cells were seeded on 6-well plates (2 × 10 5 cells/well) and cultured overnight at 37°C.…”
Section: Methodsmentioning
confidence: 99%